The Role of Competitive Environment Characteristics in Determining Strategic Options: An Analytical Study of the Opinions of a Sample of Private Bank Managers in Erbil. - سعدالله رشيد جوان; إبراهيم ولي احلام; الطائي محمد (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research aims to uncover the role of competitive environment characteristics (intensity of current competition, threat of substitute services, threat of entry of new competitors, bargaining power of suppliers, bargaining power of customers) in strategic choices (growth strategy, stability strategy, contraction strategy). The research problem was defined in several questions centered on the nature of the correlation and influence relationship between the research variables. To this end, a hypothetical research plan was developed, expressing two main hypotheses. To verify the validity of the hypotheses, all were subjected to multiple tests to confirm their validity. A questionnaire was used as a means of obtaining data. The research adopted the descriptive analysis approach to achieve the research objective and to find the relationship between the research variables. The research sample was selected from managers of several private banks in Erbil, totaling (83) managers in (25) private banks. The research reached a set of conclusions, the most important of which is the existence of a correlation and influence relationship between the variables. It recommended exploiting this relationship to serve the field under study.